Practice patterns in classic bladder exstrophy: A global perspective. Issue 4 (August 2020) - Zaman, Mohammad H.; Young, Ezekiel E.; Maruf, Mahir; Hesh, Christopher A.; Harris, Kelly T.; Manyevitch, Roni; Davis, Rachel; Wu, Wayland J.; Hall, Saran A.; DiCarlo, Heather; Gearhart, John
Summary: Introduction: While evaluation and management options for classic bladder exstrophy (CBE) patients are numerous and varied, little is known regarding the relative utilization of these different methods throughout the world. A large group of exstrophy surgeons practicing globally was surveyed, seeking to document their methods of care. Methods: A list of international exstrophy surgeons' email addresses was compiled using professional contacts and referral networking. An online survey was sent to each email address. Surgeons who had not performed a CBE closure within the previous 5 years were excluded. Survey questions queried the respondents' surgical practice type, years since training, and their preferred methods of preoperative evaluation, operative management, and postoperative management. Survey invitations were sent out starting in December 2014 and responses were collected for approximately 6 months. Results: A total of 1152 valid email addresses were invited, resulting in 293 respondents (25%) from 39 countries and every American Urological Association (AUA) section. Seventy-six were excluded, leaving 217 respondents (Table ). Respondents reported a median of 17 years since finishing their surgical training (IQR 8–25 years). Practice types included pediatric urology (n = 209), general urology (n = 9), pediatric surgery (n = 59), and other practice makeup (n = 3). On subgroup analyses, there were no significant regional practice differences, with the exception of complete primary repair of exstrophy (CPRE) and oral opioid prescribing being significantly higher in North America compared to other regions. Discussion: Findings indicate that there may be diversity in CBE practice patterns globally. While most responding surgeons from regions outside of North America indicated modern staged repair of exstrophy (MSRE) as their preferred closure technique, a relatively equal distribution of respondents from North America selected CPRE and MSRE. A majority of North American surgeons chose performing osteotomies for both newborn and delayed closures, while an appreciable number of respondents from other regions selected never using osteotomies in their closures. Limitations to this study include a low survey response rate, particularly from surgeons outside of the United States, which may have significantly impacted the ability to draw meaningful global comparisons. Conclusions: Global variation among practices of surgeons performing CBE closures may exist. The wide range of methods demonstrated by this survey suggests the need for more conclusive comparative studies to elucidate whether an optimal standard exists. Local social factors, access to surgical expertise and transportation to referral centers, and finances play a role in what constitutes the best operative approach. Table Displays the demographic characteristics of all respondents included in this survey. Table Variable Response, n(%) Years in training, median [IQR] 17 [8–25] Primary Practice type ∗   Pediatric Urology 209 (96.3%)   General Urology 9 (4.1%)   Pediatric Surgery 59 (27.2%)   Other 3 (1.4%) Region   Africa 10 (4.6%)   Asia 26 (12%)   Europe 37 (17.1%)   Middle East 9 (4.1%)   North America 121 (55.8%)   Oceania 5 (2.3%)   South America 9 (4.1%) AUA sections for US urologists   Western 13 (11%)   Northeastern 4 (3%)   North Central 30 (25%)   New England 7 (6%)   New York 4 (3%)   Mid-Atlantic 11 (9%)   Southeastern 26 (22%)   South 23 (19%) ∗ Non-mutually exclusive answer choices, percentages may sum to >100%.